(untitled) (Journal of the Bangladesh Agricultural University, 2014)
Over the last couple of decades, the old Brahmaputra River, one of the ancient river systems of Bangladesh, has fallen in verge of biodiversity changes affecting its range of fauna and flora. Study was, therefore, conducted to investigate the selectivity of fish species caught by different fishing gears used in the old Brahmaputra River system over a period of 1 year. L50% of different gears was determined mainly for dominant species where 41 fish species were recorded. Highest L50% was recorded in gill net (fash jal) followed by basket trap (vair) whereas lowest value was recorded for seine net. Seine net, cast net, sidi bair and hand line (borshi) were considered non selective gears where fash jal and sidi bair were regarded as gear specific for large fish species and koi jal, ber jal, dharma jal, howra bair and koach were considered specific for small species. Among all the gears, seine net, cast net, koi jal and howra bair were found to be harmful for small species of fishes. Monofilamentous gill net (current jal) although marked as banned gear, was found to be operated in the river and causing considerable damage to the fish stock. Fash jal was considered as harmful gear for catfish as it was found to be used to catch fishes below legal size. It is suggested that fash jal should be restricted for several months, which may allow the newly stock fingerlings to grow to market size. DOI: http://dx.doi.org/10.3329/jbau.v11i2.19940 J. Bangladesh Agril. Univ. 11(2): 359-364, 2013